The Council for Public School Improvement: From Coexistence to Collaboration in Professional Development Efforts - Anita M. Pankake; Gerald D. Bailey; Hal Rowe (Educational Considerations, 1988)
The time has come for universities and public schools to coordinate, cooperate, and collaborate in achieving mutual goals.